Analisis Kinerja Jaringan Jalan Lingkar Kota Medan - Rafiansyah, Mhd Ghaly; Rangkuti, Nuril Mahda; Lubis, Marwan (Universitas Medan Area, 2024)
The function of Ring Road is so that vehicles can reach certain parts of the city without having to go through the city center to speed up the journey. This study examines the overall traffic conditions to determine the performance of the roads and the level of service at the intersections along the Gagak Hitam ring road, Medan City. This study uses secondary data from a survey directly on the site and primary data. Peak hours are obtained on weekday afternoons at 17.00-18.00 WIB..Based on the results of the analysis, the largest value of the degree of saturation (DS) on the Gagak Hitam ring road in Medan City is 0.736 this still meets the eligibility requirements according to the standards set out in the 2014 Indonesian Road Capacity Pedoman (PKJI), which is below 0.75. Classification of the service level of the C road section where the road section is in a stable flow zone and the driver's speed selection is limited. The average delay value for signalized intersections is 51.32-59.76. Based on PM 96 of 2015 the delay value obtained is included in the category of service level of the E intersection with the condition of the delay value between 40.1 to 60 smp/sec and the performance of the intersection is bad classified.